2018
DOI: 10.1016/j.bbamem.2018.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Cause and consequence of Aβ – Lipid interactions in Alzheimer disease pathogenesis

Abstract: Self-templating propagation of protein aggregate conformations is increasingly becoming a significant factor in many neurological diseases. In Alzheimer disease (AD), intrinsically disordered amyloid-β (Aβ) peptides undergo aggregation that is sensitive to environmental conditions. High-molecular weight aggregates of Aβ that form insoluble fibrils are deposited as senile plaques in AD brains. However, low-molecular weight aggregates called soluble oligomers are known to be the primary toxic agents responsible … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
40
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 170 publications
(174 reference statements)
0
40
0
Order By: Relevance
“…Alzheimer's disease (AD) is a major cause of dementia which is characterized by a progressive cognitive and neuronal dysfunction clinically, neuroinflammation, and neuronal death (Assoc 2018; Congdon and Sigurdsson 2018). Accumulative deposits of aggregated amyloid-β peptide (Aβ) in the brain is believed to be the primary pathogenic cause of AD (Rajmohan and Reddy 2017;Rangachari et al 2018). The number the AD patients in America is expected to increase from 5.7 million today to 13.8 million by 2050 according to the World Alzheimer report.…”
Section: Introductionmentioning
confidence: 99%
“…Alzheimer's disease (AD) is a major cause of dementia which is characterized by a progressive cognitive and neuronal dysfunction clinically, neuroinflammation, and neuronal death (Assoc 2018; Congdon and Sigurdsson 2018). Accumulative deposits of aggregated amyloid-β peptide (Aβ) in the brain is believed to be the primary pathogenic cause of AD (Rajmohan and Reddy 2017;Rangachari et al 2018). The number the AD patients in America is expected to increase from 5.7 million today to 13.8 million by 2050 according to the World Alzheimer report.…”
Section: Introductionmentioning
confidence: 99%
“…In this work we investigated whether the resistance to amyloid beta aggregation in the naked mole-rat can be traced back to specific properties of the lipid membranes of this animal, given that it is well established that lipid membranes can affect the aggregation of amyloid beta [10][11][12]13 . For example, there is a strong link between cholesterol and Alzheimer's disease, which could be related to the interaction between amyloid beta with lipid membranes [14][15][16] .…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that the effects of lipids on amyloid aggregation are diverse, among which modulating of aggregation pathways is the most significant. 19 The charged membranes act as two-dimensional aggregation-templates to initiate the soluble random coil monomeric peptides to aggregate into β-sheet oligomers at a faster rate for native peptide. However, ThT kinetics suggests that the fibril elongation from the oligomeric state is inhibited in the presence of lipid bilayers.…”
mentioning
confidence: 99%